Characterisation of synthesized protected fat from used cooking palm oil and palm olein for animal feed application - K, Mohamad Asrol; I B, Suyub; M S, Pak Dek; S, Sumita; S, Jusoh (Malaysian Palm Oil Board, 2024)
In the present work, a new protected fat was produced from used cooking palm oil (UCO) by using modified fusion method. Used cooking oil protected fat (UCOPF) was compared with produced palm olein protected fat (POPF) and commercial protected fat (CPF). The quality of protected fat produce was investigated using Fourier transform infrared (FTIR) and X-ray diffraction (XRD) studies. FTIR and XRD results confirmed the well-formation of protected fat from UCO and the XRD analysis revealed fatty acid from UCO bind well with calcium ion. FTIR spectroscopy indicated carboxylate bands at 1542 and 1575 cm–1 showed the calcium ions associated with the COO- ions in the monodendate and bidendate structures in PF. Differential scanning calorimetry (DSC) study was conducted to find out the thermal behaviour of the produced UCOPF and the results clearly indicated good thermal stability. DSC indicated onset of melting at 151°C and 148°C for samples prepared UCOPF and POPF, respectively and it was slightly lower than CPF (157°C). Smooth and porous surfaces morphology of UCOPF and POPF was confirmed using scanning electron microscope (SEM) analysis. From the results it was evident that UCO can be utilised to produce protected fat as a safe animal feed.